2004
DOI: 10.1080/14767050412331283139
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–fetal status of copper, iron, molybdenum, selenium and zinc in patients with gestational diabetes

Abstract: We speculate that altered maternal-fetal status of some essential trace elements in gestational diabetes patients could have deleterious influences on the health of the mother as well as the fetus and newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 16 publications
2
43
2
1
Order By: Relevance
“…The serum selenium concentrations of Hungarian healthy pregnant women are lower than most results reported in the literature [4,18,[23][24][25][26][27], although comparison of selenium concentrations is rendered more difficult by measurements of selenium in different compartments and at different gestational weeks (Table 4).…”
Section: Discussioncontrasting
confidence: 62%
“…The serum selenium concentrations of Hungarian healthy pregnant women are lower than most results reported in the literature [4,18,[23][24][25][26][27], although comparison of selenium concentrations is rendered more difficult by measurements of selenium in different compartments and at different gestational weeks (Table 4).…”
Section: Discussioncontrasting
confidence: 62%
“…For instance, hemoglobin concentrations in pregnancy were positively associated with the risk of GDM in some (42,45,61,62,67) although not all studies (41,43,47,50,56,57,59). Studies examining serum iron concentration in relation to GDM risk have also been conflicting with mixed reports of positive (31,41,45,47), negative (68), or no association (59,69,70) with GDM status. However, the majority of these studies were of small sample size, and inferences from these studies were further limited by insufficient control for potential confounders, such as prepregnancy BMI.…”
Section: Other Indicators Of Iron Status and Gdm Riskmentioning
confidence: 96%
“…However, the majority of these studies were of small sample size, and inferences from these studies were further limited by insufficient control for potential confounders, such as prepregnancy BMI. Despite these limitations, a meta-analysis (48) pooling data from 7 studies (31,41,45,47,59,70,71) including 337 GDM cases showed that women with GDM had higher concentrations of serum iron than those without (pooled mean difference: 200 mg/L; 95% CI: 147, 253). Future prospective studies of large sample sizes and with a comprehensive adjustment of potential confounders are warranted to further investigate the roles of these iron indicators in the development of GDM.…”
Section: Other Indicators Of Iron Status and Gdm Riskmentioning
confidence: 99%
“…Selenium is involved in processes that protect the cell against oxidative damage by peroxides produced from lipid metabolism [4]. There is an increased requirement for selenium during pregnancy, presumably for fetal growth, which manifests as decreasing maternal blood and tissue selenium concentrations [5,6]. These decreases are greater in pregnant women with gestational or pre-existing diabetes.…”
Section: Introductionmentioning
confidence: 98%
“…These decreases are greater in pregnant women with gestational or pre-existing diabetes. A lower level of selenium has been described in GDM, and it has been shown that there was a inverse relationship with this trace element status and glucose tolerance [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%